Human papillomavirus vaccination access, coverage and dropout in the Federal District: a time series study, 2013-2023 - Matheus Santos Melo; Thaís Tâmara Castro e Minuzzi-Souza; Laís de Morais Soares; Allan Dantas dos Santos; Tainá Raiol; Ana Ribeiro (Epidemiologia e Serviços de Saúde)
Abstract Objective: o analyze the temporal trend of human papillomavirus (HPV) vaccination access, coverage and dropout the Federal District, Brazil, from 2013 to 2023. Methods: This is a time series study using data made available by the Brazilian National Immunization Program and the Federal District Health Department. Vaccination access, coverage and abandonment indicators were calculated. The segmented linear regression method was applied to analyze temporal trends. Results: A total of 705,823 doses were administered, 484,386 (68.6%) in females and 221,437 (31.4%) in males. Access, with average annual percentage change (AAPC) of -4.6, (confidence interval [95%CI] -8.3; -3.8), and coverage (AAPC -9.2; 95% CI -12.4; -6.6) decreased during the study period. Dropout increased (AAPC 14.1; 95%CI 11.5; 20.0). Despite the reduction in dropout observed among males (AAPC -7.7; 95%CI -10.5; -5.4), there was an increase in dropout among females (AAPC 8.9; 95%CI 4.8; 13.2). Conclusion: There was a reduction in HPV vaccination access and coverage and an increase in dropout rates, especially among females. Strategies to reverse these trends must be prioritized.